Effect of Glycine Betaine as a Growth Promoter and Stress Mitigator in Brassica oleraceavar. Italica - Sana Liaqat; Ashir Masroor; filza ghafoor; Zunaira Maqsood; Waseem Tasleem; Ashbeel ghafoor (Journal La Lifesci, 2020)
Glycine betaine performs a crucial role as an osmoprotectant and, also acts as a cytoplasmic osmotic solute specifically in the members of family Gramineae and Chenopodiaceae. Brassica oleracea var. Italica due to the presence of glucosinolates and various other chemicals, plays vital roles for humans. GB when applied to broccoli mitigate the stress effects and increase the shoot fresh and dry weight, shoot length, root dry weight, shoot calcium, potassium, nutrient uptake of sodium, calcium, potassium, SOD, peroxidase, and total soluble proteins of broccoli (Brassica oleracea var. Italica). Implementation of GB also enhanced the performance of various parameters such as antioxidant photosynthetic pigments (chlorophyll a, b, a/b, carotenoids, and total chlorophyll), and mineral nutrient use efficiency, nutrient uptake of sodium, calcium and catalase activity.